Numerical simulation on anti-freezing performance of PCM-Clay in core wall during winter construction. (October 2022) - Liu, Donghai; Liang, Jianyu; Wang, Youle
Highlights: Numerical simulation on anti-freezing performance of PCM-Clay in a core-wall unit. Analysis on temperature distribution of different PCM-Clays under diverse weathers. 8% PCM-Clay can delay freezing moment for at least 4 h in core wall construction. Abstract: The clay directly incorporated with phase change material (PCM-Clay) can prevent core-wall surface from freezing thanks to the latent heat, which is potential to extend the freezing hysteresis time of earth-rock dams in cold regions. The indoor thermal test requires time and effort to prepare different PCM-Clay samples with a tedious procedure to control temperature and fails to completely imitate the actual conditions during the core wall construction process. It is also a challenge to get the utmost out of the latent heat of PCM while prevent the PCM-Clay from freezing. Aiming to solve the above-mentioned problems, this paper proposed a numerical method for simulating the anti-freezing performance of PCM-Clay considering the actual condition of core-wall construction unit during winter construction according to a verified numerical model of indoor thermal test. Based on the proposed method, the temperature profiles of different PCM-Clays in core wall were simulated under the compulsory suspension weather required in specification and extreme weather from local meteorological record, respectively. Results show that: (1) the model efficiencies of temperature for PCM-Clay at different paraffin contents in numerical simulation reach 0.92 and above; (2) 8% PCM-Clay is able to prevent the core wall from freezing under the compulsory suspension weather and extend a freezing hysteresis time of 4.0 h under the extreme weather; (3) freezing hysteresis time of core-wall PCM-Clay decreases with the wind speed under compulsory suspension weather. This paper overcomes the defect of indoor thermal test where the actual environment for core-wall winter construction cannot be completely reproduced and temperature profiles of PCM-Clay at different paraffin contents in core-wall construction unit are analysed, providing a basis for the utilization of PCM-Clay to prevent core wall from freezing during winter construction.